Isolation of seed-borne fungi of sorghum (Sorghum vulgare pers.) - Panchal, V H; Dhale, D A (Journal of Phytology, 2011)
Sorghum (Sorghum vulgare Pers.) is the fifth most important cereal crop in the world after wheat, rice, maize and barley. The grain had been used for consumption of both humans and livestock and also different genes of the plant serve many other important uses. The crop has been suffer from various type of diseases, majority of them are known to be caused by fungi, which are mostly seed born. In present study Seed-borne fungi of sorghum in Marathwada region were surveyed. A total of 24 seed samples of eight different varieties from various locations, collected were tested, using the blotter and agar plate methods. Twenty eight fungal species of eighteen genera appeared in the seeds of eight different variety of Sorghum. In untreated seeds of the entire varieties maximum incidence was of Curvularia lunata. Treated seeds showed complete absence of Cladosporium herbarum, Trichothecium roseum and Absidia ramose. Agar plate method was found to be favorable for the maximum counts of saprophytic fungi and also favorable for detection of some specific fungi. Presence of many pathogenic fungi in considerable number of seed samples indicates the need of field surveys for these and other pathogens.Â 